Problems with choosing a mate in Islam for people who choose a mate through Social Media - Musda Asmara; Lilis Sahara (Islamic Research Publiser, 2022)
: This study aims to determine the problem of choosing a mate through social media. This research is included in the type of descriptive qualitative research. The data collection technique used in this research is documentation. This study concludes that there are many problems and consequences that occur when deciding to choose a mate through social media. This can be a lesson for all women and men not to decide to choose a mate through social media. Because in Islam, all steps toward marriage have been regulated. Choosing a mate through social media has the potential to cause harm. The provisions for choosing a mate have been explained in the hadith that choosing a partner is based on four things, 1) because of wealth, 2) offspring, 3) beauty, and 4) religion. Furthermore, in the election on social media, many disadvantages occur because there are many disadvantages compared to the benefits, the law for choosing a mate through Social Media is haram.